HUBUNGAN TEMPAT PENAMPUNGAN AIR MINUM DAN FAKTOR LAINNYA DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI PROVINSI DKI JAKARTA DAN BALI (Analisis data Riskesdas 2007) - Hasyimi, M.; Ariati, Yusniar; Hananto, Miko (Badan Penelitian dan Pengembangan Kesehatan, 2011)
In Indonesia, the incidence of Dengue Hemorrhagic fever (DHF) is significanly increasede every year. Alathough in 2008 was decreased. Incidence rate (IR) in 2006 is 52.48 to 71.78 in 2007.Untill now, there is no specific drugs and vaccine for DHF. So DHF eradication very depend on effort the principle vector Aedes aegypti control.The DHF vector breeds in water containers. Thus the relationship of individual characteristic, population density and condition of drinking container as risk factors of DHF collected in Riskesdas 2007 is useful to be analysed to DHF cases in Province of DKI Jakarta (excluding Kepulauan Seribu district) and Province of Bali,both of them as the DHF endemic area. The variable is the condition of drinking containers which commonly used in family, easily to achieve clean water, founding factors like gender, age, education, their job, quintile, resident clasification, and population density. The analysis result shown that existence of drinking container in DKI Jakarta and Bali Province, both of opened and closed clean water and drinking container is not significant difference with DHF cases (p=0,486; ? = 5%) to the incidence of DHF . All of independent variable isn?t shown significant difference with DHF cases, except for age group (p=0.014 ; ? =5%) is shown significant difference between age group was associated with the incidence of DHF.